Development of broad‐spectrum human monoclonal antibodies for rabies post‐exposure prophylaxis. Issue 4 (18th March 2016) - De Benedictis, Paola; Minola, Andrea; Rota Nodari, Elena; Aiello, Roberta; Zecchin, Barbara; Salomoni, Angela; Foglierini, Mathilde; Agatic, Gloria; Vanzetta, Fabrizia; Lavenir, Rachel; Lepelletier, Anthony; Bentley, Emma; et al.
Abstract: Currently available rabies post‐exposure prophylaxis (PEP) for use in humans includes equine or human rabies immunoglobulins (RIG). The replacement of RIG with an equally or more potent and safer product is strongly encouraged due to the high costs and limited availability of existing RIG. In this study, we identified two broadly neutralizing human monoclonal antibodies that represent a valid and affordable alternative to RIG in rabies PEP. Memory B cells from four selected vaccinated donors were immortalized and monoclonal antibodies were tested for neutralizing activity and epitope specificity. Two antibodies, identified as RVC20 and RVC58 (binding to antigenic site I and III, respectively), were selected for their potency and broad‐spectrum reactivity. In vitro, RVC20 and RVC58 were able to neutralize all 35 rabies virus (RABV) and 25 non‐RABV lyssaviruses. They showed higher potency and breath compared to antibodies under clinical development (namely CR57, CR4098, and RAB1) and commercially available human RIG. In vivo, the RVC20–RVC58 cocktail protected Syrian hamsters from a lethal RABV challenge and did not affect the endogenous hamster post‐vaccination antibody response. Synopsis: Post‐exposure prophylaxis of rabies virus infections relies on vaccination and local administration of expensive human or equine rabies immunoglobulins. Their limited supply, however, restricts access in endemic areas. Two novel human broadly neutralizing monoclonal antibodies offer hope. The replacement of rabies immunoglobulins (RIGs) with monoclonal antibody‐based post‐exposure prophylaxis (PEP) must be based on the identification of neutralizing monoclonal antibodies (mAbs) able to recognize G protein sequences of RABV from all lineages. According to WHO recommendations, the best approach to replace RIGs is to develop a cocktail of mAbs recognizing distinct antigenic sites to reduce the risk of PEP failure. RVC20 and RVC58 human mAbs were selected to recognize different antigenic sites and to broadly and potently neutralize multiple lineages of RABVs and non‐RABV lyssavirus species. These two mAbs could be produced cost‐effectively and in large quantities to be made available at affordable prices in low‐income countries. Abstract : Post‐exposure prophylaxis of rabies virus infections relies on vaccination and local administration of expensive human or equine rabies immunoglobulins. Their limited supply, however, restricts access in endemic areas. Two novel human broadly neutralizing monoclonal antibodies offer hope.